(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This article provides a comprehensive exploration of translation units and shifts as key concepts within the realm of translation studies. By synthesizing insights from prominent works in the field and emphasizing the importance of these concepts in ensuring accuracy and cultural sensitivity in translation, the author offers an insightful analysis for scholars and practitioners alike. The article not only elucidates the essence of translation units and shifts but also highlights the challenges faced by translators and suggests effective strategies to overcome them. Through a nuanced examination of these fundamental concepts, readers are encouraged to deepen their understanding of cross-linguistic communication and appreciate the intricate dynamics at play in the translation process.